Teachers’ Increased Use of Informational Text: A Phenomenological Study of Five Primary Classrooms - Heather D. Young; Christian Z. Goering (Educational Considerations, 2018)
The purpose of this phenomenological study was to explain how the Common Core State Standards may have influenced teachers' practices and philosophies regarding literacy instruction. Conducted in five kindergarten through second-grade classrooms within one elementary school, this research study collected semi-structured interviews, classroom observations, and teacher-reported lesson plans over fourteen weeks. We observed that one of the largest instructional shifts due to the implementation of new standards was in the area of informational text use. This change came about not due to the volume of empirical research stating the benefits of such texts, but rather because of an educational policy change. These findings hold implications for K-12 schools and for teacher education programs which are, in many instances, caught between the research, policies, and practice.
Keywords: informational text; Common Core State Standards; elementary education; phenomenology; standards-based reform; education policy